A Review and Bibliometric Analysis on Applications of Microbial Degradation of Hydrocarbon Contaminants in Arctic Marine Environment at Metagenomic and Enzymatic Levels - Verasoundarapandian, Gayathiri; Wong, Chiew-Yen; Shaharuddin, Noor Azmi; Gomez Fuentes, Claudio German; Zulkharnain, Azham; Ahmad, Siti Aqlima (My University, 2021)
The globe is presently reliant on natural resources, fossil fuels, and crude oil to support the world's energy requirements. Human exploration for oil resources is always associated with irreversible effects. Primary sources of hydrocarbon pollution are instigated through oil exploration, extraction, and transportation in the Arctic region. To address the state of pollution, it is necessary to understand the mechanisms and processes of the bioremediation of hydrocarbons. The application of various microbial communities originated from the Arctic can provide a better interpretation on the mechanisms of specific microbes in the biodegradation process. The composition of oil and consequences of hydrocarbon pollutants to the various marine environments are also discussed in this paper. An overview of emerging trends on literature or research publications published in the last decade was compiled via bibliometric analysis in relation to the topic of interest, which is the microbial community present in the Arctic and Antarctic marine environments. This review also presents the hydrocarbon-degrading microbial community present in the Arctic, biodegradation metabolic pathways (enzymatic level), and capacity of microbial degradation from the perspective of metagenomics. The limitations are stated and recommendations are proposed for future research prospects on biodegradation of oil contaminants by microbial community at the low temperature regions of the Arctic.
Keywords: hydrocarbon degradation; microbial community; arctic marine; review; bibliometric analysis